EXPANSION PATHS OF DECORATIVE AND FLOWER CULTURE IN THE COMPOSITION OF THE URBAN FLORA OF ASTANA CITY - Konysbayeva, D.T.; Myrzabayeva, M.T.; Gorbulya, V.S.; Suyundikova, Zh.T. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The formation of recreational zones in the territory of modern cities poses a number of problems for landscaping professionalsincluding both the preservation of the individual appearance of the city, and the introduction of new highly decorative crops, planting of already proven beautifully flowering plants while simultaneously organizing care for the plants, allowing them to delight city dwellers for a long time with green foliage, bright flowers, and pleasant aromas. The adaptation period for planted decorative plants is challenging due to the harsh ecological conditions of urbanized areas that weaken the plants' resistance to environmental abiotic and biotic factors. Important factors in extending the viability of decorative plants include obtaining and planting healthy seedlings and planting material, using biotechnology achievements, and the use of biogenic silica that enhances plant viability and resistance to exogenous stresses, mitigating toxic effects caused by abiotic stresses. Objective: To diversify the assortment of decorative cultures in the conditions of Astana city; strengthening adaptation mechanisms through the use of ... silicon-containing natural mineral.
Пути расширения декоративной и цветочной культуры в составе городской флоры города Астаны
Keywords: decorative cultures; urban flora; silicon; environmental conditions; city landscaping